South Africa's social assistance intervention as a building block of a developmental state - Chagunda, Chance Arisitaliko (Department of Social Development, 2014)
This study explores the extent to which South Africa's social assistance programme can constitute a building block of a developmental state. Using a critical research approach and Taylor's conceptual framework (2002) that draws on Sen's understanding of development as freedom, I explore the impact of cash transfers on households, on access to socio-economic opportunities and to the overall development of local democracy. Sen's capability approach and theoretical analysis of development helps to link different dimensions of poverty with human and institutional capabilities. There are five research objectives: examining whether a cash transfer has a developmental impact on the people who receive it; establishing whether cash transfers improve opportunities for households to take part in socio-economic activities; investigating how cash transfers promote civic participation and local democracy; ascertaining ways in which cash transfers promote development; and ascertaining the extent to which a cash transfer could be a significant feature of a developmental state. The findings are in two parts. The first is a review of the relevant literature. Previous studies have found that social grants can lead to poverty reduction, help to send dependents to school and enable respondents to get loans to start their own businesses. The second part consists of new findings, based on interviews from a purposive sample of 160 men and women from Khayelitsha and Graafwater in the Western Cape who received a social grant. The respondents perceived the cash transfer as opening up socio-economic opportunities for them, such as skills training. Social grants also reportedly enabled women to break free of abusive relationships and function independently, which they described as restoring their human dignity and freedom. Further, 46% indicated that the social grant income assisted them to become active citizens. A minority of respondents, especially those with small businesses or employment, perceive the grants as a backup in case of business failure or retrenchment. My assumption of cash transfers having a developmental impact has been confirmed. In conclusion, the thesis expands the theoretical and policy understanding of social assistance beyond its impacts on income poverty and provides new insights on the multiple ways through which cash transfers enable poor household members to participate in enterprise development and in building local democracy. Based on the findings, recommendations are offered to government and stakeholders.